What are you afraid of? - Ivy, Alexandra (Zebra romantic suspense., 2018)
Carmen Jacobs, who interviewed the world's most terrifying serial killers for her best-selling book, turns to Griffin Archer, a reclusive software millionaire, for help when she begins receiving terrifying tokens from a murderer.